Parent-Directed Approaches to Enrich the Early Language Environments of Children Living in Poverty - Leffel, Kristin; Suskind, Dana (Seminars in Speech and Language, 2013)
Children's early language environments are critical for their cognitive development, school readiness, and ultimate educational attainment. Significant disparities exist in these environments, with profound and lasting impacts upon children's ultimate outcomes. Children from backgrounds of low socioeconomic status experience diminished language inputs and enter school at a disadvantage, with disparities persisting throughout their educational careers. Parents are positioned as powerful agents of change in their children's lives, however, and evidence indicates that parent-directed intervention is effective in improving child outcomes. This article explores the efficacy of parent-directed interventions and their potential applicability to the wider educational achievement gap seen in typically developing populations of low socioeconomic status and then describes efforts to develop such interventions with the Thirty Million Words Project and Project ASPIRE (Achieving Superior Parental Involvement for Rehabilitative Excellence) curricula.
Keywords: Low socioeconomic status; disparities; early language; intervention; parent implemented